REFORMASI ADMINISTRASI PERPAJAKAN DI ERA DIGITIAL: KAJIAN PUSTAKA TENTANG EFEKTIVITAS SISTEM ADMINISTRASI DAN PERAN PENGAWASAN HUKUM DALAM MENINGKATKAN PENERIMAAN NEGARA - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
Tax administration reform in the digital era is a strategic transformation by the Indonesian Directorate General of Taxes to improve efficiency, transparency, and state revenue through the implementation of the Core Tax System, e-Filing, e-Billing, and the integration of big data analytics. This literature review analyses the effectiveness of the digital administration system, which has successfully accelerated tax return processing by up to 90 per cent, increased the tax-to-GDP ratio to 11.3 per cent, and contributed to a 300 per cent increase in revenue from e-commerce since 2020. In addition, the role of legal supervision through the KUP Law, ITE Law, PDP Law, and the collaboration between BPK-KPK-DJP recovered Rp 25 trillion from violations in 2024, reduced the tax ratio to 5 per cent, and created a deterrent effect that encouraged 97 per cent voluntary compliance. This descriptive-analytical qualitative study concludes that the synergy between digital technology and adaptive legal oversight is key to fiscal optimisation towards the target of Rp 1,900 trillion by 2025, with recommendations to strengthen digital literacy and AI-blockchain regulations for sustainable inclusivity.